Associations of postpartum mother-infant bonding with maternal childhood maltreatment and postpartum mental health: a cross-sectional study - Franziska Lehnig; Michaela Nagl; Holger Stepan; Birgit Wagner; Anette Kersting (BMC, 2019)
Abstract Background After delivery, some women experience impairment of their mother-infant bonding (MIB), which can lead to long-term disturbances of the mother-child relationship and the child's social-emotional development. Little is known about the association between early maternal bonding problems and mothers' own adverse childhood experiences, even though the hypothesis of the intergenerational transmission of caregiving indicates continuity in parenting quality across generations. Therefore, the current study aimed at examining the relationship between maternal childhood maltreatment and postpartum MIB, controlling for the role of postpartum mental health. Methods From February 2014 to March 2015, 725 women completed self-report measures 2 months postpartum. Maternal childhood maltreatment was assessed with the Childhood Trauma Questionnaire, postpartum depression with the Revised Beck Depression Inventory, postpartum anxiety with the Symptom Checklist-90-Revised, and postpartum MIB with the abridged version of the Postpartum Bonding Questionnaire. Data were analysed using a hierarchical regression analysis. Results Almost 46% of the included women reported at least one type of childhood maltreatment with emotional neglect being most prevalent. 13% displayed at least mild postpartum depressive symptomatology and 20% scored above the 75th percentile for postpartum anxiety. In the final regression model, which explained 29% of variance, higher severity of maternal emotional neglect in childhood, higher levels of postpartum depression and higher education were significantly related to more postpartum MIB impairment. In contrast, higher severity of maternal physical neglect was significantly associated with less postpartum MIB impairment. Conclusions This study is the first to explore the relationship between diverse types of maternal childhood maltreatment and postpartum MIB, adjusting for postpartum mental health. Maternal experiences of emotional neglect and postpartum depressive symptoms could serve as indicators to identify and support mothers with heightened risk for bonding problems, but results need to be validated in longitudinal studies.